Implementation of Discourse Network Analysis Related to News regarding PT Pertamina's Consumer Needs, Satisfaction, and Engagement - Adji Achmad Rinaldo Fernandes; Solimun Solimun; Lailil Muflikhah (International Journal of Mathematics and Mathematical Sciences)
The purpose of this study is to implement Discourse Network Analysis (DNA) and analyze the results in the formation of networks related to issues and actors in a news regarding consumer needs, satisfaction, and attachment to PT Pertamina. This study is the qualitative method that applies a qualitative Discourse Network Analysis (DNA) approach. Sources of DNA data come from various information in cyberspace (mass media, journals, articles, etc.) that are by the research context. Based on the search results in cyberspace, we obtained about 68 relevant news sources discussing consumer service on BBM products PT. Results of DNA taken from 68 news stories in cyberspace show that there are 45 actors from 14 different organizations who have opinions about PT Pertamina's consumers. Two actors only have a negative opinion, two actors have positive and negative opinions, and 41 actors have a positive opinion about the main issue of consumer needs. And we obtained 74 issues from the news obtained grouped into 3 main issues, namely, consumer needs, consumer satisfaction, and consumer engagement. And from 45 actors obtained from online news sources, they are grouped into 11 actor themes. Based on DNA results, it can be seen that there are several variables that have a possible influence on customer service. Variables that are likely to affect customer service include consumer needs, consumer satisfaction, and consumer engagement. The originality of this research lies in the application of DNA regarding consumer needs, satisfaction, and attachment to PT Pertamina.